Covalent Immune Proximity-Induction Strategy Using SuFEx-Engineered Bifunctional Viral Peptides - McCann, Harrison (My University, 2023)
Harnessing the immune system is a powerful tool in chemical biology and is the focus of cancer immunotherapy. Often, this is accomplished through monoclonal antibodies which recognize and recruit immune effector cells to an over-expressed cancer antigen presented at the cancer cell surface. More recently, there has been great interest in developing small molecule therapeutics which replicate this, but with lower developmental costs, greater modularity, and improved tumor penetration. One such class of therapeutics are bifunctional molecules known as antibody recruiting molecules, which form molecular bridges between two targets, i.e., a cancer receptor and antibody. Limitations in ternary complex formation between bifunctional molecules and their two binding targets has presented the need for increasing residence time at key junctions. Demonstrated here is the development of a covalent proximity-induction approach which leverages molecular recognition to drive an electrophilic warhead near a nucleophile within a target antibody binding site. Subsequent irreversible labeling reprograms these antibodies with tumor binding handles in situ for enhanced tumor opsonization and immune clearance mechanisms. This was accomplished by equipping a viral peptide epitope with a sulfur (VI) fluoride exchange electrophile to irreversibly label anti-herpes simplex virus (HSV) antibodies. Using the aryl sulfonyl fluoride warhead, we demonstrate fast and selective labeling for both model monoclonal antibodies, as well as natural polyclonal anti-HSV antibodies. Covalently reprogrammed antibodies elicited superior potency at both lower concentrations and with cell lines having lower antigen presentation. This proof of concept has broad applicability in developing covalent bifunctional molecules for bridging one or more protein:protein interactions.
Keywords: Immunology; Cancer; Bifunctional; Covalent; Proximity; Peptide